2017
DOI: 10.3390/nu9050491
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Stunting among Children Aged 0 to 59 Months from the Central Region of Mozambique

Abstract: The objective of this study was to identify the major socio-demographic, health, and environmental determinants of stunting among children aged 0–59 months from the Tete province (Mozambique) and offering useful information for future healthcare strategies and interventions. A case-control study was conducted among 282 (162 boys; 120 girls) children under five years of age from the central region of Mozambique between 1 May and 3 June 2014. Children with stunting (HAZ < −2 SD according to the WHO Child Growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
40
3
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 58 publications
25
40
3
9
Order By: Relevance
“…In the present study, although the highest OR for stunting correspond to children belonging to families with six or more children the same was not confirmed in the multiple analysis after adjustment by other factors. These results are contrary to other studies [9,22,29,30], which observed a significant relationship between stunting and number of under five children in a household.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, although the highest OR for stunting correspond to children belonging to families with six or more children the same was not confirmed in the multiple analysis after adjustment by other factors. These results are contrary to other studies [9,22,29,30], which observed a significant relationship between stunting and number of under five children in a household.…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of stunting among children under five was 40% and was more prevalent among male children than female children. This finding is similar to other studies conducted around the world that have also documented higher prevalence of stunting in boys than in girls [7][8][9]. According to Chirande et al [5] sex differences could also be attributed to behavioural patterns of communities for instance, favouritism towards daughters.…”
Section: Discussionsupporting
confidence: 89%
“…Research on stunting, from the Bangladesh perspective, can also be conducted for seeking explanations of why the stunting status of children varies across different divisions within Bangladesh. stunted [41,42]. The findings of this study confirm this argument in the sense that due to inadequate income, children from poor income families have higher odds in terms of switching from better to worse stunting status in comparison to children from middle income and wealthy families.…”
Section: Discussionsupporting
confidence: 78%
“…Open defecation has been closely linked to higher risk for stunting (Danaei et al, 2016;García Cruz et al, 2017;Torlesse et al, 2016;WHO, UNICEF, & USAID, 2015) because the human fecal substances provide pathways for flies and domestic animals to spread bacteria into residences and eating utensils and further lead to diarrhea. For children in their early childhood, frequently dealing with diarrhea increases the likelihood of stunting as they lose the nutrient they have absorbed and the depletion of their intestinal wall (Mbuya & Humphrey, 2016).…”
Section: Resultsmentioning
confidence: 99%